Improving Models of Care for Diabetes in Pregnancy: Experience of Current Practice in Far North Queensland, Australia - McLean, Anna; Kirkham, Renae; Campbell, Sandra; Whitbread, Cherie; Barrett, Jennifer; Connors, Christine; Boyle, Jacqueline; Brown, Alex; Mein, Jacqueline; Wenitong, Mark; McIntyre, H. David; Barzi, Federica; et al. (Frontiers in Public Health, 2019)
Aims: To map health practitioners' experiences and describe knowledge regarding screening and management of Diabetes in Pregnancy (DIP) in Far North Queensland, Australia. Methods: Mixed methods including a cross-sectional survey (101 respondents) and 8 focus groups with 61 health practitioners. All participants provided clinical care for women with DIP. Results: A wide range of healthcare professionals participated; 96% worked with Indigenous women, and 63% were from regional or remote work settings. Universal screening for gestational diabetes at 24–28 weeks gestation was reported as routine with 87% using a 75 g Oral Glucose Tolerance Test. Early screening for DIP was reported by 61% although there was large variation in screening methods and who should be screened <24 weeks. Health practitioners were confident providing lifestyle advice (88%), dietary, and blood glucose monitoring education (67%, 81%) but only 50% were confident giving insulin education. Electronic medical records were used by 80% but 55% also used paper records. Dissatisfaction with information from hospitals was reported by 40%. In the focus groups improving communication and information technology systems were identified as key areas. Other barriers described were difficulties in care coordination and access for remote women. Conclusions: Communication, information technology systems, coordination of care, and education for health professionals are key areas that will be addressed by a complex health systems intervention being undertaken by the DIP Partnership in North Queensland.